Pneumomediastinum with COVID-19: a natural process or complication? A literature review - Kanani, Elmutaz (International Surgery Journal, 2020)
COVID-19 pneumonia is a serious respiratory viral infection that recently spread all over the world. It carries a significant mortality risk. Little is known about the pathophysiology of the disease, being a newly mutated virus. Knowledge of the clinical disease manifestations kept evolving as unfamiliar findings and presentations are constantly reported. Pneumomediastinum had been frequently reported since the start of the pandemic, and its significance was questioned. The aim of this review is to analyze the reported cases of pneumomediastinum with coronavirus infection to look for its pathophysiology, prognostic value, and best treatment. A systematic literature search was conducted using free text search for pneumomediastinum with COVID-19 case reports and case series. PubMed and Google scholar data bases were searched. Twenty three articles were retrieved. All are case reports and case series, 39 cases of the reported cohort qualified for inclusion into analysis. Chronic respiratory conditions were found in 23% of the patients. There was about five folds risk of developing the condition with oxygen therapy (both through invasive and non-invasive means). The best diagnostic modality was chest computed tomography scan (74.4%). Management was conservative in 69%, while pleural drainage was necessary in 23% of the patients. Both treatment strategies were successful with no statistical difference (p value=0.327). It is not yet clear if pneumomediastinum is a pathological disease process or an interventional complication. Interventional and conservative treatment had similar outcomes depending on individual case merits. No prognostic value could be demonstrated.